Higher volume endovascular stroke centers have faster times to treatment, higher reperfusion rates and higher rates of good clinical outcomes. (13th May 2012) - Gupta, Rishi; Horev, Anat; Nguyen, Thanh; Gandhi, Dheeraj; Wisco, Dolora; Glenn, Brenda A; Tayal, Ashis H; Ludwig, Bryan; Terry, John B; Gershon, Raphael Y; Jovin, Tudor; Clemmons, Paul F; et al.
Abstract : Background and purpose: Technological advances have helped to improve the efficiency of treating patients with large vessel occlusion in acute ischemic stroke. Unfortunately, the sequence of events prior to reperfusion may lead to significant treatment delays. This study sought to determine if high-volume (HV) centers were efficient at delivery of endovascular treatment approaches. Methods: A retrospective review was performed of nine centers to assess a series of time points from obtaining a CT scan to the end of the endovascular procedure. Demographic, radiographic and angiographic variables were assessed by multivariate analysis to determine if HV centers were more efficient at delivery of care. Results: A total of 442 consecutive patients of mean age 66±14 years and median NIH Stroke Scale score of 18 were studied. HV centers were more likely to treat patients after intravenous administration of tissue plasminogen activator and those transferred from outside hospitals. After adjusting for appropriate variables, HV centers had significantly lower times from CT acquisition to groin puncture (OR 0.991, 95% CI 0.989 to 0.997, p=0.001) and total procedure times (OR 0.991, 95% CI 0.986 to 0.996, p=0.001). Additionally, patients treated at HV centers were more likely to have a good clinical outcome (OR 1.86, 95% CI 1.11 to 3.10, p<0.018) and successful reperfusion (OR 1.82, 95% CI 1.16 to 2.86, p<0.008). Conclusions: Significant delays occur in treating patients with endovascular therapy in acute ischemic stroke, offering opportunities for improvements in systems of care. Ongoing prospective clinical trials can help to assess if HV centers are achieving better clinical outcomes and higher reperfusion rates.